FAKTOR RESIKO KEJADIAN IKTERUS PADA BAYI BARU LAHIR: LITERATURE REVIEW: FAKTOR RESIKO KEJADIAN IKTERUS PADA BAYI BARU LAHIR: LITERATURE REVIEW - fatma, inge devita; Rahayu, Yustina; Ayumni, Noviana; Hamidah, Najma Ummu (LPPM STIKes Bahrul Ulum Jombang, 2021)
Background: The indicator value of public health is assessed from the number of maternal mortality (MMR) and infant mortality (IMR). One of the contributors to infant mortality is icterus neonatorum. Icterus neonatorum is a yellow discoloration of the skin, eye membranes, and mucous membranes where the cause is too much bilirubin in the blood. If untreated, neonatal jaundice can cause brain damage (kernicterus) which can lead to mental retardation, cerebral palsy, and even death. The purpose of this study was to determine the risk factors that influence the occurrence of jaundice in neonates. Subjects and Methods: This research is a literature review from various national and international journal articles. Search articles using databases: PubMed, and Google Scholar. This method aims to enrich insight into risk factors for jaundice in BBL by summarizing the theory discussed. The method used will present new analytical facts and literature reviews by summarizing well-published articles that are also relevant, then compare the summary results in tabular form. Results: from 10 national and international articles, it was found that the risk factors for jaundice in neonates include low birth weight, premature birth, perinatal complications of infection, asphyxia, ABO incompatibility, and drug history, adequacy of breastfeeding, low vitamin E levels, delivery with oxytocin induction. Conclusion: risk factors for neonatal jaundice include low birth weight, premature birth, perinatal complications of infection, asphyxia, ABO incompatibility, drug history, adequate breastfeeding, low vitamin E levels, oxytocin-induced labor.